Behavioral risk elicits selective activation of the executive system in adolescents: Clinical implications - Yaxley, Richard H.; Van Voorhees, Elizabeth E.; Bergman, Sara; Hooper, Stephen R.; Huettel, Scott A.; De Bellis, Michael D. (Frontiers in Psychiatry, 2011)
We investigated adolescent brain processing of decisions under conditions of varying risk, reward and uncertainty. Adolescents (n = 31) preformed a Decision-Reward Uncertainty task that separates decision uncertainty into behavioral and reward risk, while they were scanned using functional magnetic resonance imaging (fMRI). Behavioral risk trials involved uncertainty about which action to perform to earn a fixed monetary reward. In contrast, during reward risk the decision that might lead to a reward was known, but the likelihood of earning a reward was probabilistically determined. Behavioral risk trials evoked greater activation than the reward risk and no risk conditions in the anterior cingulate, medial frontal gyrus, bilateral frontal poles, bilateral inferior parietal lobe, precuneus, bilateral superior-middle frontal gyrus, inferior frontal gyrus, and insula. Our results were similar to those of young adults using the same task (Huettel, 2006) except that adolescents did not show significant activation in the posterior supramarginal gyrus during behavioral risk. During the behavioral risk condition regardless of reward outcome, overall mean frontal pole activity showed a positive correlation with age during the behavioral and reward risk conditions suggesting a developmental difference of this region of interest. Additionally, reward response to the Decision-Reward Uncertainty task in adolescents was similar to that seen in young adults (Huettel, 2006). Our data did not show a correlation between age and mean ventral striatum activity during the three conditions. While our results came from a healthy high functioning non-maltreated sample of adolescents, this method can be used to address types of risks and reward processing in children and adolescents with predisposing vulnerabilities and add to the paucity of imaging studies of risk and reward processing during adolescence.